2021
DOI: 10.1017/dmp.2021.265
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Hospital Evacuation From a Hospital Within 5 km Radius of Fukushima Daiichi Nuclear Power Plant: A Retrospective Analysis of Disaster Preparedness for Hospitalized Patients

Abstract: Emergency evacuation during disasters may have significant health impacts on vulnerable populations. The Japanese Government issued evacuation orders for surrounding residents of the Fukushima Daiichi nuclear power plant (FDNPP) immediately after the March 11, 2011, nuclear accident. Little is known of difficulties associated with the disaster-specific evacuation from health care facilities located in this area. Among the 338 patients hospitalized at Futaba Hospital, located 4.6 km west of FDNPP, at the time o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 14 publications
(15 reference statements)
0
24
0
Order By: Relevance
“…After 12 March, there were 129 seriously ill patients who could not move independently in the hospital, while only a few people could provide health care. This was mainly because the staff of the hospital had to accompany the first emergency hospital evacuation, as well as the delay in assisting with subsequent evacuations due to lack of proper communication and immediate post-disaster confusion [ 27 ]. As a result, the hospital was seriously lacking in human resources, and it may have been difficult to provide nutritional support to patients requiring central intravenous nutrition and tube feeding, and to properly manage newly emerging diseases, such as aspiration pneumonia [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…After 12 March, there were 129 seriously ill patients who could not move independently in the hospital, while only a few people could provide health care. This was mainly because the staff of the hospital had to accompany the first emergency hospital evacuation, as well as the delay in assisting with subsequent evacuations due to lack of proper communication and immediate post-disaster confusion [ 27 ]. As a result, the hospital was seriously lacking in human resources, and it may have been difficult to provide nutritional support to patients requiring central intravenous nutrition and tube feeding, and to properly manage newly emerging diseases, such as aspiration pneumonia [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the outage of infrastructure made it difficult to continue various types of health care, as exemplified by the need to manually adjust the rate of intravenous drips due to the power outage and the increased frequency of care required due to manual suction care, in addition to the lack of human resources before waiting for subsequent evacuation. Other studies have reported that the water outage at the hospital may have prevented adequate toilet care and cleanliness [ 19 ], and the unavailability of telephone service may have made it difficult to communicate with the external bodies and delays in receiving assistance [ 27 , 31 ]. Prior studies have reported that post-disaster infrastructure outages can cause lack of oxygen care [ 34 ], lack of heat stroke care due to air conditioning outages [ 35 ], lack of temperature control due to lack of heating equipment [ 29 , 30 ], problems related to securing drinking water and using toilets [ 36 , 37 ], and lack of care for dialysis patients [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations